Dual-gate low-voltage organic transistor for pressure sensing. (23rd January 2017) - Tsuji, Yushi; Sakai, Heisuke; Feng, Linrun; Guo, Xiaojun; Murata, Hideyuki
Abstract: We simultaneously achieved low-voltage operation (−5 V) and large drain current ( I D ) modulation in a dual-gate organic pressure sensor in which a piezoelectric layer was stacked on a low-voltage organic field-effect transistor (OFET). During testing, I D changed from 3.9 × 10 −9 to 2.5 × 10 −11 A when a 300 kPa pressure load was applied, and I D clearly responded to the pressure load and release. An endurance cycle test of the device was performed using a pressure load of 100 kPa, and the I D modulation was consistently reproduced throughout the test.